Utilization of ladle furnace slag and fly ash as partially replacement of cement - Thwe, Khin Sam; Ayawanna, Jiratchaya; Mase, Lindung Zalbuin; Chaiyaput, Salisa (My University, 2025)
Ladle Furnace Slag (LFS) and fly ash (FA) are industrial waste products commonly deposited in landfills, while the cement industry is a major source of carbon dioxide (CO2) emissions. Previous research has explored using LFS and FA as cement replacement materials to help mitigate environmental impacts. Yet, no studies have explored combining LFS and FA as cement replacement materials. Therefore, this research highlights the study of the combination of LFS and FA mixes as a partial cement replacement. The mix design for cement replacement materials was developed by combining ordinary Portland cement (OPC), LFS, and FA in the following weight ratios: 10:10:80, 20:20:60, and 30:30:40. These mix designs were assessed in comparison to 100%OPC (% by weight), evaluating key properties (bulk density, specific gravity, normal consistency, setting time, compressive strength, flexural strength, and microstructural characteristics). According to the findings, incorporating LFS and FA, both pozzolanic materials effectively improved the strength of the material by promoting a pozzolanic reaction, particularly during the final stages of curing. Furthermore, it was found that a mixed design containing 20% OPC, 20% LFS, and 60% FA demonstrated suitable properties for cement replacement in various applications, with beneficial results in terms of setting time and strength development. From X-ray fluorescence (XRF) and scanning electron microscope (SEM analysis), C-S-H gel, as well as Ca(OH)2 and Mg(OH)2 chemical compounds, were formulated. The aforementioned replacement is being used to promote environmental sustainability through the efficient use of industrial byproducts.
Keywords: Cement replacement; Fly ash; Ladle furnace slag; Microstructure; Strength